IMPACT OF GOVERNMENT POLICY ON FORMAL EDUCATION OF MINANGKABAU AND NIAS ETHNICITY FISHERMEN’S CHILDREN IN INDONESIA - Fitri Eriyanti; Zikri Alhadi; Engkizar Engkizar; Isnarmi Moeis; Muhammad Agus Yussof; Risnaldi Ibrahim (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
This research aims to analyze how the impact of government policy on formal education of traditional fishermen children. In this research, the author took a study of two ethnicity groups namely Minangkabau and Nias ethnicity in Padang City. The research uses quantitative methods with a survey approach. The research data was taken through a questionnaire to the families of traditional Minangkabau and Nias ethnicity fishermen who were selected based on a Simple Random Sampling technique. All data were analyzed by descriptive analysis using SPSS 18.00 software. The results of the study found that the impact of government policy had affected the formal education of Minangkabau ethnicity fishermen children, even the children's education reached the level of college. But for Nias ethnicity, it does not affect their child's formal education. The difference between the results of government policies on these two ethnicity groups is actually motivated by the cultural factors of both ethnicities. For Minangkabau parents and children, education is something that is so important for the future, on the contrary for parents and children of Nias ethnicity, education is considered less important.